Factors affecting human security: A focus on community security in West Gondar Administrative Zone - Tsehay, Babey; Abay, Abyssinia (Ethiopian Journal of Social Sciences, 2024)
This study examines the factors influencing human security, with a specific focus on community security in the West Gondar Administrative Zone (WGAZ). The research investigates various human security issues and the role of the government in addressing them. A qualitative research approach, employing in-depth single case study design was utilized incorporating both primary and secondary sources of data. Primary data were collected through key informant interviews, focus group discussions (FGDs) and observations; while secondary data were obtained from published and unpublished materials. The data were thematically analyzed, identifying key themes related to human security problems and the government's involvement in WGAZ. The analysis revealed that factors such as ethnic conflicts, territorial disputes, human trafficking, illegal migration, arms proliferation, contraband trade, property theft, kidnappings, insurgent activities, resource conflicts, and government weaknesses contribute to human insecurity in WGAZ. The study recommends strengthening local state institutions, particularly the security sector, building trust between the community and authorities, and urging the federal government to address external threats and resolve border demarcation issues with Sudan. The findings of this research contribute to a better understanding of human security challenges and provide insights into effective interventions in WGAZ and similar contexts.